2013
DOI: 10.1186/2193-1801-2-251
|View full text |Cite
|
Sign up to set email alerts
|

Predictive impact of polymorphism of PNPLA3 on HCC development after interferon therapy in Japanese patients with chronic hepatitis C

Abstract: The impact of single-nucleotide polymorphisms (SNP) of patatin-like phospholipase domain-containing protein 3 (PNPLA3) on development of hepatocellular carcinoma (HCC) is not clarified for Japanese patients with chronic hepatitis C. The present study investigated the associations of rs738409 PNPLA3 with HCC development after the antiviral therapy with peg-interferon and ribavirin for Japanese patients with hepatitis C virus serotype 1 and high viral load. Of the 271 patients enrolled in the study, 20 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
6
2
Order By: Relevance
“…In contrast, the potential association between PNPLA3 rs738409 and HCC risk in patients with HCV‐related cirrhosis remains controversial . The association between this variant and HCC risk in HCV‐related cirrhosis was either marginal in our case–control study or negative in our prospective cohort.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In contrast, the potential association between PNPLA3 rs738409 and HCC risk in patients with HCV‐related cirrhosis remains controversial . The association between this variant and HCC risk in HCV‐related cirrhosis was either marginal in our case–control study or negative in our prospective cohort.…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast, the potential association between PNPLA3 rs738409 and HCC risk in patients with HCV-related cirrhosis remains controversial. [38][39][40][41] The association between this variant and HCC risk in HCV-related cirrhosis was either marginal in our case-control study or negative in our prospective cohort. We observed the same results for TM6SF2 rs58542926 that was not associated with HCC development in casecontrol or prospective cohort of HCV-related cirrhosis.…”
Section: Discussioncontrasting
confidence: 53%
“…PNPLA3 polymorphisms have been reported to be associated with hepatic steatosis, inflammation, fibrosis, and carcinogenesis in NAFLD (Romeo et al 2008 ; Rotman et al 2010 ; Valenti et al 2010 ; Sookoian and Pirola 2011 ; Burza et al 2012 ; Kawaguchi et al 2012 ; Kitamoto et al 2013 ). PNPLA3 polymorphisms have also been reported to be associated with hepatic steatosis, fibrosis, treatment response, and carcinogenesis in CHC (Valenti et al 2011 ; Trepo et al 2011 ; Cai et al 2011 ; Valenti et al 2012 ; Clark et al 2012 ; Dunn et al 2014 ; Ezzikouri et al 2014 ; Moritou et al 2013 ; Zampino et al 2013 ; Trepo et al 2014 ; Sato et al 2013 ). However, several reports have not found an association of PNPLA3 polymorphisms with fibrosis and carcinogenesis in CHC (Trepo et al 2011 ; Nischalke et al 2011 ; Rembeck et al 2012 ; Miyashita et al 2012 ; Takeuchi et al 2013 ; Nakamura et al 2013 ; Guyot et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis performed by Trepo et al showed that a PNPLA3 polymorphism was strongly associated with HCC, although the association was stronger in patients with alcoholic liver disease (OR = 2.20; 95% CI: 1.802.67; P = 4.71 × 10 −15 ) than that in patients with CHC (OR = 1.55; 95% CI: 1.03–2.34; P = 3.52 × 10 −2 ) (Trepo et al 2014 ). In Japanese studies, Moritou et al reported that a PNPLA3 polymorphism was significantly associated with serum AFP level (Moritou et al 2013 ), and Sato et al reported that the median time between HCV infection and the development of HCC was significantly shorter for patients with the PNPLA3 GG genotype in HCV-related HCC (Sato et al 2013 ). The results of our present study confirmed an association between PNPLA3 and the development of HCC in Japanese patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, AFP value is sometimes elevated in CHC patients without HCC [23][24][25] . [26] . Elevated AFP values may therefore combine with several risk factors other than cancer.…”
Section: Discussionmentioning
confidence: 99%